Behavioral Economics: A New Lens for Understanding Genomic Decision Making. Issue 3 (24th April 2018) - Moore, Scott Emory; Ulbrich, Holley H.; Hepburn, Kenneth; Holaday, Bonnie; Mayo, Rachel; Sharp, Julia; Pruitt, Rosanne H.
Abstract: Purpose: This article seeks to take the next step in examining the insights that nurses and other healthcare providers can derive from applying behavioral economic concepts to support genomic decision making. As genomic science continues to permeate clinical practice, nurses must continue to adapt practice to meet new challenges. Decisions associated with genomics are often not simple and dichotomous in nature. They can be complex and challenging for all involved. Design: This article offers an introduction to behavioral economics as a possible tool to help support patients', families', and caregivers' decision making related to genomics. Methods: Using current writings from nursing, ethics, behavioral economic, and other healthcare scholars, we review key concepts of behavioral economics and discuss their relevance to supporting genomic decision making. Findings: Behavioral economic concepts—particularly relativity, deliberation, and choice architecture—are specifically examined as new ways to view the complexities of genomic decision making. Each concept is explored through patient decision making and clinical practice examples. This article also discusses next steps and practice implications for further development of the behavioral economic lens in nursing. Conclusions: Behavioral economics provides valuable insight into the unique nature of genetic decision‐making practices. Clinical Relevance: Nurses are often a source of information and support for patients during clinical decision making. This article seeks to offer behavioral economic concepts as a framework for understanding and examining the unique nature of genomic decision making. As genetic and genomic testing become more common in practice, it will continue to grow in importance for nurses to be able to support the autonomous decision making of patients, their families, and caregivers.